Analysis of Strengthening Beam Structure Case Study on Food Court Building of Ruang Terbuka Hijau (RTH) Project at Alun-Alun Kota Kediri - Khoirul Walad; Afrikhatul Maulidiyah; Januar Sasongko (CV. Publikasi Indonesia, 2024)
The Green Open Space (RTH) construction in Kediri City includes a food court building utilizing reinforced concrete structures. During construction, cracking issues occurred in several beam structures due to the inability to bear the design loads effectively, necessitating a strengthening approach. This study aims to develop and evaluate a strengthening method for cracked beam structures by employing concrete jacketing. The specific objective is to improve the structural integrity and load-bearing capacity of these beams to ensure the durability and safety of the building. A concrete jacketing technique was used to reinforce the cracked beams, utilizing K-300 ready-mix concrete and additional reinforcing steel. The study involved structural analysis to assess the load-bearing capacity before and after jacketing, and on-site evaluation was conducted to monitor the method's effectiveness. The findings indicate that the jacketing method significantly increased the beams' bending moment capacity and overall structural strength, successfully addressing the cracks and enhancing the beams' ability to bear the intended loads. The reinforced beams showed improved load distribution and structural resilience performance. Concrete jacketing proved to be an effective method for strengthening the cracked beam structures in the Green Open Space project. The study provides valuable insights for similar future construction projects, suggesting that concrete jacketing can be a reliable reinforcement technique to enhance the durability and safety of building structures.